Computer crime on the Internet : lessons learned and re-learned - Choong, Calvin Tze Wei. (2010)
This dissertation focuses on computer crimes and security considerations on the Internet. Computer break-ins are getting very common these days. Log files and even program binaries are changed, making it very difficult for system administrators to assess the damage and track down the intruders. A detailed study on some of these hacks are covered and special attention is paid to the methods crackers use to break into computer systems and what they did once they were in.